ادبی ترجمہ اور بین الثقافتی مکالمہ: تحقیقی و تنقیدی جائزہ (Al-Aasar, 2025)
This research paper explores the significance of literary translation in facilitating intercultural dialogue, particularly within the context of Urdu literature. Literary translation acts as a bridge between cultures, offering a medium for sharing stories, values, and traditions. The study critically examines the challenges faced by translators in preserving the essence of the original text while making it accessible to different cultural audiences. Furthermore, it delves into the role of literary translation in promoting cross-cultural understanding and appreciation. Through a comprehensive analysis, this paper highlights the transformative power of translation in shaping intercultural relations and its potential to foster global empathy and cooperation.